Higher prevalence of exercise-associated hyponatremia in female than in male open-water ultra-endurance swimmers: the `Marathon-Swim` in Lake Zurich - Wagner, S.; Knechtle, B.; Knechtle, P.; Rüst, C. A.; Rosemann, T. (European Journal of Applied Physiology, 2012)
We investigated the prevalence of exercise-associated hyponatremia (EAH) in 25 male and 11 female open-water ultra-endurance swimmers participating in the `Marathon-Swim` in Lake Zurich, Switzerland, covering a distance of 26.4 km. Changes in body mass, fat mass, skeletal muscle mass, total body water, urine specific gravity, plasma sodium concentration [Na+] and haematocrit were determined. Two males (8%) and four females (36%) developed EAH where one female was symptomatic with plasma sodium [Na+] of 127 mmol/L. Body mass and plasma [Na+] decreased (p < 0.05). The changes in body mass correlated in both male and female swimmers to post-race plasma [Na+] (r = -0.67, p = 0.0002 and r = -0.80, p = 0.0034, respectively) and changes in plasma [Na+] (r = -0.68, p = 0.0002 and r = -0.79, p = 0.0039, respectively). Fluid intake was neither associated with changes in body mass, post-race plasma [Na+] or the change in plasma [Na+]. Sodium intake showed no association with either the changes in plasma [Na+] or post-race plasma [Na+]. We concluded that the prevalence of EAH was greater in female than in male open-water ultra-endurance swimmers.